(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2004)
Finite element program using solid cube elements for concrete and bar elements for steel reinforcement was developed in order to analyze the behavior of confined reinforced concrete columns with circular cross section under increasing compression load. The concrete was assumed as elastic- plastic material and follow Von Mises failure criterion with associated flow rule. The steel reinforcement was considered as linear strain hardening material. Experimental results were used to verify the numerical results.